A researcher's guide to the Swedish compulsory school reform - Helena Holmlund (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
This paper demonstrates how a natural experiment in education can be used to estimate causal effects. The Swedish compulsory school reform extended basic education gradually across cohorts and municipalities, allowing for a difference-in-differences analysis. The paper summarizes the literature using this reform and shows that it provided individuals from low socio-economic backgrounds with better opportunities in life. Not only did they attain higher levels of education - they also earned higher earnings, were less likely to participate in crime, and more likely to run for office.
Keywords: I24; I26; I28; 330; education reform; natural experiment